2012
DOI: 10.1371/journal.pone.0047414
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Early Proliferative Response of the Rodent Bladder to Subtotal Cystectomy: A Unique Model of Mammalian Organ Regeneration

Abstract: Subtotal cystectomy (STC; surgical removal of ∼75% of the rat urinary bladder) elicits a robust proliferative response resulting in complete structural and functional bladder regeneration within 8-weeks. The goal of these studies was to characterize the early cellular response that mediates this regenerative phenomenon, which is unique among mammalian organ systems. STC was performed on eighteen 12-week-old female Fischer F344 rats. At 1, 3, 5 and 7-days post-STC, the bladder was harvested 2-hours after intrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…To date, growth factors incorporated into scaffolds have been selected based on known activities in a variety of organ systems. Ongoing studies by a number of groups are characterizing the molecular events that occur both in regenerating tissue following injury [67, 69, 96] and during development [67] to better understand how this knowledge could be exploited for tissue engineering.…”
Section: Modulation Of Scaffold Properties With Trophic Factorsmentioning
confidence: 99%
“…To date, growth factors incorporated into scaffolds have been selected based on known activities in a variety of organ systems. Ongoing studies by a number of groups are characterizing the molecular events that occur both in regenerating tissue following injury [67, 69, 96] and during development [67] to better understand how this knowledge could be exploited for tissue engineering.…”
Section: Modulation Of Scaffold Properties With Trophic Factorsmentioning
confidence: 99%
“…Understanding the mechanisms and characteristics of functional recovery will be a key to designing improved therapeutics for bladder and organ regeneration in the future. (C) Colocalization in cells of incorporated BrdU (bromodeoxyuridine), indicative of proliferation, and specific markers for smooth muscle (SMA, smooth muscle actin) in the muscularis propria (MP) of the regenerating bladder of a female rat [the panel was reproduced from Peyton et al (2012); additional details can be found in the manuscript as well]. Confocal z-stack reconstruction imaging was performed at 600Â magnification, where offset pictures are digitally zoomed.…”
Section: Pharmacology Of Regenerative Medicinementioning
confidence: 99%
“…A more recent follow up study (Peyton et al, 2012) used fluorescent bromodeoxyuridine (BrdU) labeling to quantify the spatiotemporal characteristics of the proliferative response that mediates the functional regeneration observed by Burmeister et al (2010), as occurs during the critical first week post-STC. In this study, less than 1% of cells in the bladder wall were labeled with BrdU in control bladders under resting conditions (i.e., no damage), but this percentage increased significantly, by 5-to 8-fold, at all time points post-STC.…”
Section: A Bladder Diseasementioning
confidence: 99%
“…Several studies have suggested that removal of a large part of the bladder without replacement results in some degree of functional bladder regeneration in both rats [ 17 22 ] and humans [ 23 32 ]. As such, we have focused our recent efforts on developing rodent models and methods that can provide additional insight into the cellular and molecular mechanisms responsible for functional bladder regeneration in mammals.…”
Section: Introductionmentioning
confidence: 99%